Analisis Kualitatif Kesalahan Konseptual Senyawa Ionik dan Senyawa Kovalen dalam Argumentasi Mahasiswa pada Laporan Praktikum Kimia Dasar - Ni'mah, Fatchiyatun; Sari, Anggi Ristiyana Puspita; Anggraeni, Maya Erliza; Theasy, Yoan (Jurnal Ilmiah Kanderang Tingang, 2024)
Understanding the concept of ionic and covalent compounds is a fundamental foundation in basic chemistry education, as these concepts underpin the structure, properties of compounds, and their applications in daily life. Misconceptions about ionic and covalent bonding are common and negatively impact students' ability to analyze compound properties, critical thinking skills, and scientific argumentation. On the other hand, Generation Z demonstrates weaknesses in deeply reflecting on conceptual errors, as evident in basic chemistry lab reports. Lab reports can reveal both the depth of understanding and the patterns of conceptual errors experienced by students. This study aims to analyze students' conceptual errors related to ionic and covalent compounds in Basic Chemistry I lab reports. The research employs a case study method with a qualitative descriptive approach. The researcher acts as an instrument to assess students' conceptual errors by discussing their lab reports. The findings reveal three conceptual errors in the sub-topic of melting point comparison and five conceptual errors in the sub-topic of solubility.